The Complete Business Guide for a Successful Medical Practice - Baum, Neil; Bonds, Roger G.; Crawford, Thomas; Kreder, Karl J.; Shaw, Koushik; Stringer, Thomas; Thomas, Raju (Springer International Publishing : Imprint: Springer, 2015)
This text provides physicians with the basic business skills in order for them to become involved in the financial aspect of their practices. The text will help the physician decide what kind of practice they would like to join (i.e. private practice, small group practice, solo practice, hospital employment, large group practice, academic medicine, or institutional\government practice) as well as understand the basics of contracting, restrictive covenants, and how to navigate the road to partnership. Additional topics covered include, monthly balance sheets, productivity, overhead costs and profits, trend analysis and benchmarking. Finally, the book provides advice on advisors that doctors will need to help with the business of their professional and personal lives. These include accountants, bankers, lawyers, insurance agents, and other financial advisors. The Complete Business Guide for a Successful Medical Practice provides a roadmap for physicians to be not only good clinical doctors but also good businessmen and businesswomen. It will help doctors make a difference in the lives of their patients as well as sound financial decisions for their practice. Thank-you!